The Effect of Liquidity and Leverage on Profitability with Covid 19 as a Moderating Variable - Apriani, Ani; Rufiatun, Yayuk; Gulo, Yanto Nius (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of liquidity and leverage on profitability with Covid19 as a moderating variable in transportation and logistics companies. This type of research uses an associative method with a quantitative approach. The data used in this study are secondary data. The sampling technique is purposive sampling. The number of samples in this study based on the criteria obtained was 132 data for 11 periods with the Eviews 12 testing tool. The analysis technique used was panel data regression and the Sobel test. The results of this study indicate that Liquidity has an effect on Profitability; Leverage does not have a significant effect on Profitability; Covid19 moderates the effect of liquidity on Profitability; Covid19 moderates the effect of leverage on Profitability.